2019
DOI: 10.1016/j.apcatb.2019.01.081
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CO addition on the toluene total oxidation over Co based mixed oxide catalysts

Abstract: Renaud.Cousin@univlittoral.fr A Hydrotalcite like compounds containing Co, Al and Ce were synthesized by coprecipitation. The mixed oxides obtained after calcination were characterized by several techniques: XRD, BET, H2-TPR and XPS. The activities of the mixed oxides were evaluated in the total oxidation of toluene in presence or in absence of carbon monoxide. The benzene, benzyl alcohol and benzaldehyde are the principal byproducts observed during the toluene oxidation in presence of CoAl(Ce) mixed oxides.Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 43 publications
(62 reference statements)
2
20
0
Order By: Relevance
“…[ 48,49 ] It has been reported that O α concentration (O α /(O α + O β ) is directly related to the catalytic performance. [ 50,51 ] The catalyst with higher O α proportion is expected to have better oxygen storage capacity and mobility. [ 52 ] The calculated results in Table 2 show that the proportion of O α on CuOA surface is the lowest, which is ≈22.3% and those of CuOU and CuOH are almost the same (≈24%).…”
Section: Resultsmentioning
confidence: 99%
“…[ 48,49 ] It has been reported that O α concentration (O α /(O α + O β ) is directly related to the catalytic performance. [ 50,51 ] The catalyst with higher O α proportion is expected to have better oxygen storage capacity and mobility. [ 52 ] The calculated results in Table 2 show that the proportion of O α on CuOA surface is the lowest, which is ≈22.3% and those of CuOU and CuOH are almost the same (≈24%).…”
Section: Resultsmentioning
confidence: 99%
“…Co 2+ [28,29]. The promoted catalytic performance of Cu 0.05 Co and Ni 0.05 Co for toluene oxidation could be attributed to the strong synergistic effect between cobalt and doped metal cations.…”
Section: Discussionmentioning
confidence: 95%
“…This may be due to the formation of byproducts and adsorption on the surface of the catalyst, after a period of time, the generated byproducts desorbed from the surface of the catalyst. [ 53 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] Therefore, it is urgent to find a valid method to improve the catalytic performance of Co 3 O 4 catalysts. In order to further improve the catalytic performance of Co 3 O 4 catalyst, various hybrid cations (such as Mn 3+ , [ 14 ] Fe 3+ , [ 15 ] Ni 2+ , [ 16 ] La 3+ , [ 17 ] Al 3+ , [ 18 ] and In 3+[ [ 19 ] ] ) were recommended to form a mixed‐metal oxide with strong synergistic effect between Co and hybrid metal cations. For example, the addition of Mn gave Co 3 O 4 catalyst large surface area, rich cationic vacancy, and enhanced oxygen mobility, which greatly improved the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%